Economics meets sociology in strategic management - Baum, Joel A. C.; Dobbin, Frank (Advances in strategic management ;, 2000)
The last several years has witnessed a growing interaction between economists and sociologists engaged in the study of organizations' strategies. Economists and sociologists can gain real insight from these interactions. To date, however, these interactions have been to ad hoc and unfocused to bear any real fruit. This volume moves the discussion to the next level by focusing the discussion, and taking a step toward systematizing some of the relationships between economic and sociological approaches to strategic management. To accomplish this, the volume reprints four 'matched pairs' of influential articles on firms' strategies in economic sociology and strategic management and use these articles to frame a conversation between the articles' pioneering authors and other prominent researchers in strategic management and sociology working on closely-related research problems. Each pair of articles followed by provocative essays - inspired by the pairing - written by the articles' original authors. Two contextualizing commentaries penned by influential strategy and organizations researchers - one grounded in strategic management and one in economic sociology - extend each conversation. A reflective reply from the articles' authors concludes the conversation - for now. A framing introduction and concluding epilogue, written by volume editors Joel Baum and Frank Dobbin, set the stage both for the volume and for future conversations between the disciplines in strategic management.